Cultural Identity in Contemporary Children’s Literature: A Jungian Archetypal Analysis of A Lucky Chinese New Year - Sharenlie, Grania; Chang, Gabrielle Angela; Djohan, Febrina Stevani; Surya, Michaella Isabel; Maradona, Amadea Krista; Widjaya, Yemima Candice (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2024)
This research investigates how archetypes within children's literature not only reinforce cultural traditions and values in collective unconsciousness of individuals, but also emphasize the role of family unity and generational continuity in maintaining cultural heritage in a modern, globalized context in the preservation of cultural identity within the children's book